Relative Contributions of Pseudohypoxia and Inflammation to Peritoneal Alterations with Long-Term Peritoneal Dialysis Patients - Krediet, Raymond T; Parikova, Alena (Clinical journal of the American Society of Nephrology, 2022)
Long-term peritoneal dialysis is associated with alterations in peritoneal function, like the development of high small solute transfer rates and impaired ultrafiltration. Also, morphologic changes can develop, the most prominent being loss of mesothelium, vasculopathy, and interstitial fibrosis. Current research suggests peritoneal inflammation as the driving force for these alterations. In this review, the available evidence for inflammation is examined and a new hypothesis is put forward consisting of high glucose-induced pseudohypoxia. Hypoxia of cells is characterized by a high (oxidized-reduced nicotinamide dinucleotide ratio) NADH-NAD+ ratio in their cytosol. Pseudohypoxia is similar but occurs when excessive amounts of glucose are metabolized, as is the case for peritoneal interstitial cells in peritoneal dialysis. The glucose-induced high NADH-NAD+ ratio upregulates the hypoxia-inducible factor-1 gene, which stimulates not only the glucose transporter-1 gene but also many profibrotic genes like TGFβ, vascular endothelial growth factor, plasminogen activator inhibitor-1, and connective tissue growth factor, all known to be involved in the development of peritoneal fibrosis. This review discusses the causes and consequences of pseudohypoxia in peritoneal dialysis and the available options for treatment and prevention. Reducing peritoneal exposure to the excessively high dialysate glucose load is the cornerstone to avoid the pseudohypoxia-induced alterations. This can partly be done by the use of icodextrin or by combinations of low molecular mass osmotic agents, all in a low dose. The addition of alanyl-glutamine to the dialysis solution needs further clinical investigation.
Keywords: vaskulární endoteliální růstový faktor A; dialyzační roztoky; Dialysis Solutions; pseudohypoxia; peritoneální dialýza; plasminogen activator inhibitor-1; Glucose; NAD; peritoneum; hypoxie; connective tissue growth factor; vascular endothelial growth factor; zánět; lidé; Hypoxia; Inflammation; peritoneal dialysis; Peritoneal Dialysis; Peritoneum; glucose exposure; peritoneal membrane alterations; Humans; glukosa; inflammation; Vascular Endothelial Growth Factor A